50.2k views
1 vote
5(1+s)=9s+6
----------------

User Gokkor
by
4.4k points

2 Answers

4 votes

Answer:


s=-(1)/(4)


s=-0.25

Explanation:


5\left(1+s\right)=9s+6

Apply distributive law:-


5\left(1+s\right)


=5+5s


5+5s=9s+6

Now, Subtract 5 from both sides :-


5+5s-5=9s+6-5


5s=9s+1

Subtract 9s from both sides:-


5s-9s=9s+1-9s


-4s=1

Divide both sides by -4:-


(-4s)/(-4)=(1)/(-4)


s=-(1)/(4)

OAmalOHopeO

User Penguin Egg
by
5.0k points
3 votes

Answer:

Solution given

5(1+s)=9s+6

distribute

5+5s=9s+6

subtract both side by 5s

5+5s-5s=9s-5s+6

solve like terms

5=4s+6

subtract both side by 6

5-6=4s+6-6

-1=4s

divide both side by 4

-1/4=s

User Sawe
by
5.3k points